Effect of amitriptyline on orthodontic tooth movement in rats: An experimental study - Mohammad Sadegh Ahmad Akhoundi; Mahdiyeh Shaygan-Mehr; Mohammad Ali Keshvad; Shahroo Etemad-Moghadam; Mojgan Alaeddini; Ahmadreza Dehpour; Amir Hossein Mirhashemi (Tabriz University of Medical Sciences, 2023)
In the article entitled "Effect of amitriptyline on orthodontic tooth movement in rats: an experimental study" which appeared in J Dent Res Dent Clin Dent Prospect 2020;14(3): 147- 152, doi: 10.34172/joddd.2020.033, the name of the fourth author has been misspelled. The correct spelling is Shahroo Etemad-Moghadam. The original version of the article has been updated to reflect the corrections.